2012
DOI: 10.2174/1874325001206010340
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Arthroplasty: A Systematic Review of the Literature

Abstract: Identification and management of patients with isolated patellofemoral osteoarthritis are challenging. Many of these patients present at a young age and it is important to distinguish degenerative change in the patellofemoral articulation from the other various causes of anterior knee pain. Once the diagnosis of isolated patellofemoral arthrosis has been made non-operative and conservative surgical techniques should be exhausted fully before prosthetic arthroplasty is considered. This review focuses on the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Progression of tibiofemoral OA is the most common reason for the failure of PFA using modern prosthetic designs [13,25,44]. An interesting finding of the present study was that none of the patients with an inlay component showed progression of tibiofemoral OA, whereas more than half of the patients in the inlay group demonstrated progression of medial and/or lateral tibiofemoral OA.…”
Section: Discussionsupporting
confidence: 47%
“…Progression of tibiofemoral OA is the most common reason for the failure of PFA using modern prosthetic designs [13,25,44]. An interesting finding of the present study was that none of the patients with an inlay component showed progression of tibiofemoral OA, whereas more than half of the patients in the inlay group demonstrated progression of medial and/or lateral tibiofemoral OA.…”
Section: Discussionsupporting
confidence: 47%
“…No significant progression of tibiofemoral OA or significant changes in patellar height were observed. To date, most trochlear implants can be considered as onlay designs or anterior cut prosthesis, respectively [39,54,59]. These implants are based on the trochlear cuts of a total knee arthroplasty, replacing the entire anterior trochlear surface [39].…”
Section: Discussionmentioning
confidence: 99%
“…Dahm et al [12] demonstrated that PFA has comparable clinical outcomes to TKA but with less blood loss and a shorter hospital stay. Tarassoli et al [13] noted in a systematic review that PFA has the advantage of being a less invasive operation, with quicker postoperative recovery and preservation of bone stock, with the option to convert to TKA at a later time.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential advantages of isolated PFA, the initial results of the first-generation PFA implants were not favorable, with high failure rates primarily due to mechanical failure [14e17]. McKeever originally proposed a design allowing for a Vitallium shell to replace the patella surface [13,18]. This design eventually lost favor due to concerns of the accelerated wear of the femoral trochlea cartilage.…”
Section: Discussionmentioning
confidence: 99%